Enablers and barriers towards ensuring routine immunization services during the COVID-19 pandemic: findings from a qualitative study across five different states in India. (2nd March 2022) - Patel, Kripalini; Nayak, Bhagyashree; Rana, Salaj; Krishnan, Parthiban; Tandale, Babasaheb Vishwanath; Basak, Surajit; Sinha, Abhik; Kumar, Muthusamy Santhosh; Borah, Prasant; Singh, Harpreet; Gupta, Nivedita; Dutta, Shanta; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic has led to disruption in delivering routine healthcare services including routine immunization (RI) worldwide. Understanding the enablers and barriers for RI services during a pandemic is critically important to develop context-appropriate strategies to ensure uninterrupted routine services. Methods: A community-based, cross-sectional descriptive study was conducted in five different states of India, nested within an ongoing multicentric study on RI. Telephone in-depth interviews among 56 health workers were carried out and the data were analyzed using a content analysis method. Results: During the COVID-19 pandemic, healthcare providers encountered many challenges at the health system, community and individual level when rendering RI services. Challenges like the limited availability of personal protective equipment and vaccines, deployment for COVID-19 duty at system level, the difficulty in mobilizing people in the community, fear among people at community level, mobility restrictions and limited family support, as well as the stress and stigma at individual level, were barriers to providing RI services. By contrast, the issuing of identification cards to health staff, engaging community volunteers, the support given to health workers by their families and training on COVID-19, were factors that enabled health workers to maintain RI services during the pandemic. Conclusions: When addressing the COVID-19–related public health emergency, we should not lose sight of the importance of services like RI.